Problems of Higher School Didactics: Uncut Pages - R. M. Petruneva; V. D. Vasilyeva; Y. V. Petruneva (Высшее образование в России)
Higher education today is not going through the best of times: decisions taken in the educational process at various levels (Federal Laws “On Education in the Russian Federation” of 29.12.2012 No 273-FZ and “On Amendments to the Federal Law “On Education in the Russian Federation” on the education of students” of 31.07.2020 No 304-FZ, Federal State Educational Standards of Higher Education, etc.), related to global changes taking place in society and in the world in recent decades, were made without careful didactic study. This cannot help to improve the quality of specialist training. Teachers are forced to work “by trial and error”, producing countless didactic documents. At present, identification of didactic problems in the educational process of higher educational institutions is extremely relevant due to the expansion of the field of didactic research in higher school pedagogy.The aim of the authors was to analyze some of the most relevant didactic phenomena in the digital reality that have not yet received proper understanding. As a result of the analysis, some important didactic problems of higher education are identified, concerning goal-setting, compliance of teaching with classical didactic principles, organization of distance learning in electronic informational and educational environment, mixed and project-based learning. The article also dwells on psychological problems of Internet content assimilation and “non-contact” interaction between the subjects of the educational process, etc. The most promising areas of didactic research in higher education, including the development of interdisciplinary contacts, are highlighted.